PORTRAITS IN INDONESIA: INTERNATIONAL REFUGEES FACE UNCERTAIN FUTURE (A STUDY OF INTERNATIONAL REFUGEE LAW) - Kadarudin, Kadarudin (Veritas et Justitia, 2018)
This paper discusses the issue of refugees from an international law perspective. It is known that Indonesia is not a party to either the 151 Refugee Convention as well as the 1967 Protocol, but mostly as transit country house a number of refugees running away from conflict areas in Myanmar, the Middle East and Afghanistan.  This legal research employs a juridical normative method.  By tracking down and analyzing all relevant legal sources it is revealed that Indonesia’s treatment of refuges is based on the general obligation to protect and honor human rights (on the basis of international minimum standard).  It is further recommended that Indonesia should actively support the global compact on refugees.